Study of efficacy and timing of laser suture lysis in reducing intraocular pressure after trabeculectomy with mitomycin-C - Ramakrishna, Swati (Oman J Ophthalmol, 2016)
CONTEXT: Laser suture lysis is used to enhance filtration after trabeculectomy. AIMS: The aim of this is to evaluate the change in intraocular pressure (IOP) after laser suture lysis after trabeculectomy with mitomycin-C and to correlate the efficacy of suture lysis in relation to the time of lysis. SETTINGS AND DESIGN: Prospective interventional study of seventy eyes of seventy patients. SUBJECTS AND METHODS: Trabeculectomy with mitomycin-C was performed for 352 patients with glaucoma. Laser suture lysis was carried out when indicated for seventy patients during 2(nd)–8(th) week posttrabeculectomy. Primary outcome measures were IOP at immediate postsuture lysis, 1, 2, 4, 6, and 8 weeks, 3 and 6 months following laser suture lysis. For the purpose of statistical analysis, patients were divided into three groups depending on the week of suture lysis as <3 weeks, 3(rd)–5(th) week, and >5 weeks posttrabeculectomy and 21 mmHg was used as the cutoff for the achievement of target IOP. STATISTICAL ANALYSIS USED: Descriptive statistical analysis has been carried out. Significance is assessed at 5% level of significance. Student's t-test (two-tailed, independent) has been used to find the significance of study parameters on continuous scale between two groups. Chi-square/Fisher exact test has been used to find the significance of study parameters on categorical scale between two or more groups. RESULTS: On immediate postsuture lysis, 62 patients (88.6%) had IOP of <21 mmHg which increased to 68 patients (98.6%) at the end of 6 months postsuture lysis. When laser suture lysis was performed during 3(rd)–5(th) week posttrabeculectomy, 34 patients (73.9%) achieved the target IOP. CONCLUSIONS: Laser suture lysis during 3(rd)–5(th) week posttrabeculectomy with mitomycin-C is an effective and safe technique for reducing IOP.